A long way to go ... A study on the implementation of the learning-outcomes based approach in the EU - Tim Birtwistle; Courtney Brown; Robert Wagenaar (Universidad de Deusto, 2016)
Higher Education institutions have, in the framework of the Bologna Process, been called to re-define their degree programmes on the basis of the learning outcomes approach. This implies a change of paradigm moving from teacher-centred to student-centred education. The Tuning project was set-up in 2000 to develop - through a bottom-up approach - a methodology to achieve this shift. This methodology proved not only to be relevant for Europe, but also for other world regions, including the USA, where Tuning projects were launched from 2009. In 2010 both in the EU and the USA the need was felt to find out whether the intended modernization of learning was actually taking place and how this process was perceived by its main stakeholders. For this purpose a study was initiated, covering the period 2011 to the beginning of 2016, based on the two-pillar approach of quantitative and qualitative instruments. For the study a robust evaluation instrument was developed, consisting of surveys and in-depth interviews implemented by a research team at a selected group of Higher Education institutions, involving management, teaching staff, student counsellors and students. In this paper the outcomes of the EU part of the study are presented, cross referencing to some of the USA study results. The main outcome of the study is that in general limited progress has been made regarding the intended paradigm shift and that key expectations of the reform Process have not been met. This is both the case for Europe and the USA. Although, good practices have been identified, the actual implementation of the student-centred approach is not proceeding beyond a discourse on the paradigm shift and there is no certainty it will be achieved. For Europe there is also a worrying disconnect between the various tiers of the HE sector, ranging from Ministers to students, regarding the actual penetration of the student-centred approach and the education experience of the students. There has been a failure to engage with and convince academic staff about the necessity and advantages of this paradigm shift. Teaching staff are struggling to adjust to the new concepts and paradigm shift and are challenged by no longer being the "knowledge owners" but rather learning facilitators. It does not help that the vast majority of staff members have not undertaken professional development for HE teaching. Where staff development has taken place, it is too focused on process, rather than the concepts and benefits of a learning outcomes approach. The outcomes of the study should therefore be perceived as a wake-up call because without additional and continued support in particular for the teaching staff the reform process could fail. Published online: 01 June 2016